2019
DOI: 10.37358/rc.19.2.6926
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Activated Carbon Preparation from Avocado Seeds, using the Response Surface Methodology

Abstract: Avocado seeds based activated carbon was prepared using chemical activation method which consisted of potassium hydroxide treatment. The main factors influencing the preparation of activated carbons at the calcination temperature, the concentration of the activating agent and the duration of calcination were investigated. One used as a mathematical model the response surface methodology to correlate the response. The significant factors identified by the analysis of variance (ANOVA) through the t-test, the Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…Apart from the listed peaks, AvoSE–AuNPs also showed an absorption peak at 613.44 cm –1 which is primarily due to a C–Br stretch. These results are in accordance with several studies which have identified peaks at 3330, 3000–2840, 2920, 1730, 1580, and 1150–1000 cm –1 from raw avocado seeds . The spectra indicated the presence of hydroxyl and carboxylic groups on the AvoSE–AuNPs, and this may possibly be a result of the involvement of flavonoids, terpenoids, phenolic compounds, and/or carbohydrates in the synthesis process.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Apart from the listed peaks, AvoSE–AuNPs also showed an absorption peak at 613.44 cm –1 which is primarily due to a C–Br stretch. These results are in accordance with several studies which have identified peaks at 3330, 3000–2840, 2920, 1730, 1580, and 1150–1000 cm –1 from raw avocado seeds . The spectra indicated the presence of hydroxyl and carboxylic groups on the AvoSE–AuNPs, and this may possibly be a result of the involvement of flavonoids, terpenoids, phenolic compounds, and/or carbohydrates in the synthesis process.…”
Section: Resultssupporting
confidence: 92%
“…These results are in accordance with several studies which have identified peaks at 3330, 3000− 2840, 2920, 1730, 1580, and 1150−1000 cm −1 from raw avocado seeds. 71 The spectra indicated the presence of hydroxyl and carboxylic groups on the AvoSE−AuNPs, and this may possibly be a result of the involvement of flavonoids, terpenoids, phenolic compounds, and/or carbohydrates in the synthesis process. Several studies have reported the role of hydroxyl and carboxylic acids-containing compounds in the bio-reduction, capping, and stabilization of AuNPs.…”
Section: (D) Kinetics Of Avose−aunp Synthesismentioning
confidence: 94%
“…Then, 15 g of precursor was treated using (10, 15, and 20 g) potassium hydroxide pellets (KOH, >85.0%, Mumbai, India) with (10, 15, and 20 g) potassium carbonate (K 2 CO 3 , >99.0%, Mumbai, India) in 50 mL of double-distilled water to dissolve all KOH and K 2 CO 3 . The mixture was left overnight at room temperature and then dried at 110 °C for 24 h. 30 To get stable pyrolysis temperature, 5.4 mg of dried sample was characterized by a DTG-60H simultaneous thermogravimetric and differential thermal analyzer from Shimadzu.…”
Section: Methodsmentioning
confidence: 99%
“… 1 Commonly used powdered AC has high mechanical strength and good mechanical and chemical stability. 2 Activated carbon has a wide range of biomass sources, such as coffee husk, 3 shea residue, 4 avocado seeds 5 and straws; the biomass can also be prepared as a graphene material to catalyze the production of biodiesel from microalgae lipids under solar energy. 6 Therefore, it is widely used in adsorption, separation, catalysis, medicine and other fields.…”
Section: Introductionmentioning
confidence: 99%